Case report: Cefoperazone-sulbactam induced Kounis syndrome and cardiogenic shock - Ding, Peng; Zhou, Yuan; Long, Kun-lan; Zhang, Li; Gao, Pei-yang (Frontiers in Cardiovascular Medicine, 2022)
Background: Kounis syndrome is a hypersensitive coronary artery disease caused by the body's exposure to allergens, which is induced by various drugs and environmental factors. This entity has been described primarily in isolated case reports and case series. We report a case of type Ⅲ Kounis syndrome caused by cefoperazone-sulbactam. Case presentation: A 79-year-old man who received an infusion of cefoperazone-sulbactam in the respiratory Department of our hospital for recurrent lung infections developed skin flushing on the torso and extremities 28 minutes later, followed quickly by loss of consciousness and shock. After antianaphylaxis, pressor therapy, and fluid rehydration, the patient was admitted to the ICU for treatment, during which she experienced recurrent ventricular fibrillation and a progressive increase in troponin I levels. The ECG of the patient showed that the ST segment elevation of lead Ⅱ、Ⅲ, avF and V3R-V5R was 0.10-0.20MV. An urgent coronary angiography showed an in-stent thrombosis in the middle part of the right coronary artery, occlusion of the distal flow with TIMI grade 0. The diagnosis was type Ⅲ Kounis syndrome with cardiogenic shock. Despite aggressive treatment, the patient died on day 7 after ICU admission. Conclusion: Kunis syndrome is a life-threatening disease. Allergic reactions in patients with a history of cephalosporin allergy and coronary stent implantation should be considered and treated promptly.